A Blockchain-Based Public Auditing Scheme for Cloud Storage Environment without Trusted Auditors. (5th October 2020) - Li, Song; Liu, Jian; Yang, Guannan; Han, Jinguang
Abstract : In the cloud storage applications, the cloud service provider (CSP) may delete or damage the user's data. In order to avoid the responsibility, CSP will not actively inform the users after the data damage, which brings the loss to the user. Therefore, increasing research focuses on the public auditing technology recently. However, most of the current auditing schemes rely on the trusted third public auditor (TPA). Although the TPA brings the advantages of fairness and efficiency, it cannot get rid of the possibility of malicious auditors, because there is no fully trusted third party in the real world. As an emerging technology, blockchain technology can effectively solve the trust problem among multiple individuals, which is suitable to solve the security bottleneck in the TPA-based public auditing scheme. This paper proposed a public auditing scheme with the blockchain technology to resist the malicious auditors. In addition, through the experimental analysis, we demonstrate that our scheme is feasible and efficient.